BEBERAPA PENDEKATAN SOSIOLOGIS DALAM PENELITIAN KARAWITAN - T. Slamet Suparno (FBS UNY, 2006)
Basically, several approaches from many different fields of study,such as history, philosophy, anthropology, psychology, economy and sociology,can be applied in any researches, including a research on karawitan. This writingexplains how sociological approach is applied to study karawitan. Principally,this approach analyze the relationship between society and karawitan art, itsliterary values and the social values, the artists' background and the problems ofart life in society. Several concepts and theories in sociology can be used toanalyze karawitan as the object.Key words: karawitan (a Javanese music), art and sociological approach